AN EVALUATION OF THE AUSTRALIAN ISLAMIC CENTER IN NEWPORT, MELBOURNE FROM THE PERSPECTIVE OF ARCHITECTURAL CONTEXTUALISM AND SOCIAL INCLUSION - HOO, QIOW VERN; M. RASDI, MOHD TAJUDDIN; RONG, LAU ZHENG; LOONG, YAP KUAN; ZHENG, LAW CHUAN (Human Sustainability Procedia, 2018)
This research seeks to evaluate the Australian Islamic Center at Newport, Melbournefrom theaspect of contextualism in relation to the physical urban fabric, the planning of spaces for interaction among Muslims and non-Muslims and the interpretation of historical references. In the present day, most of the manifestation of mosque architectural language is out of physical, social and historical context. The grand scale and monumental architecture shows shallow interpretation of Islam teachings and emphasize on the identity of mosque as a symbol of Islam’s past glory. As a result, the conflicts between Muslims and non-Muslims and eventually lead to grave consequences. Hence, this paper seeks to remind the mosque designers to rethink their design ideas towards the approach of contextualism by engaging the AustralianIslamic Centeras a case study because this mosque is an extraordinary example of contextual architecture in terms of adaptability in physical and social context as well as the interpretation of historical references.The methods used to obtain the information for this research paper are online research, on-site observation and photograph for evidences, literature research of the elements of traditional mosque in the past as well as the intentions of Glenn Murcutt in transferring them into modern context. Besides, interview with the second imam of the mosque and person in-charged of Islamic Council of Victoria was carried out.